France : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for France. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
A strong economic recovery is underway in France, bolstered by progress on vaccination, strong fiscal support and solid private sector led investment. Employment has recovered to above pre-crisis levels and unemployment is virtually stable. Inflation is increasing, mainly driven by a rise in energy prices but also due to supply-chain disruptions. The public deficit and debt ratio surged in 2020, reflecting the large amount of emergency support deployed and the drop in activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy